Linear Landscape Spaces in the Planning Structure of the City - Shevchenko, Luidmyla; Novoselchuk, Natalia; Toporkov, Volodymyr (International Journal of Engineering and Technology, 2018)
The article is aimed to show up the role of linear landscape spaces in the layout structure of a city. The current urban environment of existence of human shows a mix between nature, urbanized informative space, advanced innovative technologies, design elements. The authors accentuate importance of creation harmonious ecological and esthetically attractive environment of a city for human life and activities basing on the proper compatibility of these constituents. Basing on the selected methodology of research the authors analyze the available historiography material, world analogues of the investigated objects and their project conceptions. The article presents the existing theoretical conceptions of the urban development starting from the treatises of the ancient Greek philosophers up to project urban conceptions of the future cities basing on the linear landscape spaces. Position of the objects under research is outlined in the system of the green space. The system includes the objects under investigation as its integral part. The authors are educed the most widespread varieties of objects. The authors show the most widespread varieties of objects under research in the layout structure of modern cities. Particular attention of the authors is addressed to the linear parks, embankments, boulevards and parkways that play an important role in life and activity of a city and its habitants. Importance of proper implementation of project conceptions for such spaces has been shown by means of different spheres of design - landscape, ecological, ergonomics, urban and graphic.Â Â